Political Connection and Credit Risk Management: Its Effect on Bank’s Performance - Fahmi Setiadi; Y Anni Aryani (Universitas Muhammadiyah Surakarta, 2019)
The present study examines the effect of political connection and credit risk management on Indonesian bank’s performance during the declining credit growth period. The present study involved 258 banks that registered in the Indonesian Stock Exchange from 2012 to 2017 as the sample of the study. Company political connection was measured using headcount index, credit risk management was measured by its credit risk value or NPL, and the company financial performance was measured based on Return on Asset. The data of the study were obtained from banks and Indonesian Stock Exchange annual report. The result of regression analysis showed that Indonesian bank’s political connection positively and significantly affected financial performance, and credit risk significantly affected bank’s financial performance. This result implied that banks in Indonesia needs political connection and improve their credit risk management in order to improve their financial performance during the declining credit growth period. The present study reveals a new fact that in order to maintain financial performance during the declining credit growth period, banking institution may utilize their political connection and improve their credit risk management. Keywords: Political Connection, Credit Risk Management, Bank Performance, Credit Growth